Recreative activism in Romania How cultural affiliation and lifestyle yield political engagement - Rammelt, Henry; Gubernat, Ruxandra (Socio.hu Társadalomtudományi Szemle, 2017)
The present article analyzes the new culture of protest in Romania, a type of engagement we define as recreative activism. During the past years, young and culturally–inclined citizens started demanding more and more to have a share in the political process. To explain the novelty of this phenomenon, we argue that patterns of cultural consumption in the scene contributed to the spiral of ever–increasing participation in protests throughout the past six years, mainly drawing on in–depth interviews with activists and adherents of the Romanian alternative scene. This data was further supplemented by inferences derived from participative observation and content analysis. Three main protest waves were analyzed and critically put in context: the Rosia Montana (2013), Colectiv (2015), and OUG 13 (2017) protests. Our main findings are that recreative activism has its roots in the concomitance of cultural consumption and noninstitutionalized political participation, as well as in a certain disenchantment of protest participants with post–communist politics. Further, recreative activism is characteristic for nonconventional political involvement, which requires less commitment than classic activism and is less influenced by ideologies. Keywords: recreative activism, new culture of protests, cultural dimensions of collective action, Romania, Eastern Europe.